Single-walled carbon nanotubes covalently functionalized with cysteine: A new alternative for the highly sensitive and selective Cd(II) quantification - Gutierrez, Fabiana Andrea (2017)
This work is focused on the development of an electrochemical sensor for the quantification of Cd(II) based on the use of glassy carbon electrodes (GCE) modified with a dispersion of single-walled carbon nanotubes (SWCNTs) covalently functionalized with cysteine (Cys). Cd(II) is preconcentrated at the electrode surface by complex formation at open circuit potential, followed by the reduction at −0.900 V and the final anodic voltammetric stripping in a 0.020 M acetate buffer solution pH 5.00. The functionalization of SWCNTs was performed through the reaction between the carboxylic groups of oxidized SWCNT and amino groups of S-triphenylmethyl cysteine using a coupling chemistry agent based on benzotriazol for the activation of carboxylic residues. There was a linear relationship between Cd oxidation signal and Cd(II) concentration between 1.0 and 300.0 μgL−1 Cd(II), with a sensitivity of (49 ± 2) × 10−3 μAμg−1L and a detection limit of 0.3 μgL−1. The reproducibility was 1.7% using the same dispersion and 3.8% using 3 different dispersions. The sensor was challenged with groundwater samples enriched with Cd(II) showing excellent recovery percentages and excellent agreement with the values obtained by ICP-MS.